Anne of the Island - MONTGOMERY, L.M; L.M. MONTGOMERY (New York Bantam Books, 1998)
follows Anne Shirley through her four years at Redmond College in Kingsport, where she pursues a B.A.. Leaving behind her childhood in Avonlea, she experiences personal growth, friendship, career aspirations, and romantic challenges, including rejecting proposals and realizing her love for Gilbert Blythe
Keywords: marking her transition from adolescence to young adulthood. During her four years at college; self-discovery and accepting reality